Computer-Assisted Analysis and Epidemiological Value of Genotyping Methods for Campylobacter jejuni and Campylobacter coli - de Boer, Paulo (American Society for Microbiology, 2000)
For epidemiological tracing of the thermotolerant Campylobacter species C. jejuni and C. coli, reliable and highly discriminatory typing techniques are necessary. In this study the genotyping techniques of flagellin typing (flaA typing), pulsed-field gel electrophoresis (PFGE), automated ribotyping, and amplified fragment length polymorphism (AFLP) fingerprinting were compared. The following aspects were compared: computer-assisted analysis, discriminatory power, and use for epidemiological typing of campylobacters. A set of 50 campylobacter poultry isolates from The Netherlands and neighboring countries was analyzed. Computer-assisted analysis made cluster analysis possible and eased the designation of different genotypes. AFLP fingerprinting was the most discriminatory technique, identifying 41 distinct genotypes, while PFGE identified 38 different types, flaA typing discriminated 31 different types, and ribotyping discriminated 26 different types. Furthermore, AFLP analysis was the most suitable method for computer-assisted data analysis. In some cases combining the results of AFLP fingerprinting, PFGE, and flaA typing increased our ability to differentiate strains that appeared genetically related. We conclude that AFLP is a highly discriminatory typing method and well suited for computer-assisted data analysis; however, for optimal typing of campylobacters, a combination of multiple typing methods is needed.